The Establishment of Special Judicature for the Local Government Election Result Dispute - Nofi Sri Utami; M. Dwi Cahyono; Syaifuddin Syaifuddin (Universitas Muhammadiyah Ponorogo, 2020)
The election of the local government is conducted democratically and it creates many chaos. The resolution of the election disputes is carried out in Supreme Court from the Local Government. One of the democracy forms is by establishing a general election. The solution in overcoming the election of the regional head which is done in the Constitutional Court creates vagueness which then supports the creation of Special Judicature. This analysis has two problems: (1) why is the Special Judicature needed? (2) What are the rules of Special Judicature to settle the dispute of the local government election. To discuss the problems, the researcher uses the doctrinal research using normative juridical approach with deductive thinking method, positivism paradigm then it is analyzed using perspective descriptive method. The results of this analysis are (1) the reason of the creation of special judicature, whether it is Supreme Court or Constitutional Court has no power in overcoming the problem of regional election; to solve the problem there needs to be a special institution to achieve justice. (2) The rules of special judicature are substantive and structural. Substantive means that it must provide law events, structural means a form of an ad hoc. The ad hoc judge is chosen from ex Constitutional Court judge or academician who is expertise in local autonomy and general regional election law. The special judicature should be located in every province.